2018
DOI: 10.1001/jamaoto.2018.0039
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Hearing Difficulty and Risk of Accidental Injury in US Adults, 2007 to 2015

Abstract: Hearing difficulty is significantly associated with accidental injury, especially injury related to work or leisure. Increased awareness about hearing difficulty and its proper screening and management may assist in decreasing accidental injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16] However, the self-reported hearing-loss measure we used herein has been associated with injuries in previous studies, and more strongly associated with self-reported injury than pure-tone audiometry in at least one study. 29,35 Thus, we believe that self-reported hearing loss is capturing a relevant condition-hearing loss that impacts participant function-and that associations seen with self-reported hearing loss would be meaningful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9][10][11][12][13][14][15][16] However, the self-reported hearing-loss measure we used herein has been associated with injuries in previous studies, and more strongly associated with self-reported injury than pure-tone audiometry in at least one study. 29,35 Thus, we believe that self-reported hearing loss is capturing a relevant condition-hearing loss that impacts participant function-and that associations seen with self-reported hearing loss would be meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing loss was assessed using self‐reported hearing status, which may be a strength and a limitation. Self‐reported hearing status may be a more sensitive measurement of respondents' functional hearing status and its impact on their daily life than more objective measures . However, the majority of NHIS respondents who report less than “good” hearing likely do not meet an objective definition of bilateral hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 As a chronic sensory deficit, hearing loss has been linked to difficulty in physical functioning, 3 social isolation, 4 poor quality of life, 5 cognitive decline, 6 and increased risk of accidental injuries. 7 The burden of hearing loss and its associated sequela are well documented in the literature. Although many of these disabilities can result in an increased risk of death, the data on the potential association between hearing loss and risk of mortality remains inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Hearing function is crucial in detecting and protecting oneself from dangerous situations. A study on accidental injuries in self-reported hearing difficulty patients was conducted in the United States, reporting an odds ratio of 1.9 in those with a lot of trouble hearing [ 11 ]. HL patients are also more likely to experience psychiatric disorders, including depression, which may lead to suicidal behavior.…”
Section: Discussionmentioning
confidence: 99%